Cascade of Care of HIV Seroconverters in the Context of Universal “Test and Treat” - (:unkn) unknown (My University, 2017)
The ANRS 12249 TasP cluster-randomized trial aimed at evaluating the impact of a Universal Test and Treat (UTT) approach on population-based HIV incidence in rural KwaZulu Natal, South Africa. Previous results showed low rates of early linkage to HIV care and treatment and did not identify any incidence reduction. To optimize the impact of UTT, time to ART initiation and viral suppression must be shorten significantly, in particular among newly infected individuals. We describe here the longitudinal cascade of care for those seroconverting during the course of the TasP trial.Every six months between March 2012 and June 2016, resident members aged ≥16 years old were offered rapid HIV testing at home and asked independently to provide dried blood spot (DBS) samples. Those testing positive or who self-reported their positive status were referred to local trial clinics for ART initiation, regardless of their CD4 count (intervention) or according to national guidelines (control). Cases of HIV seroconversion were identified using multiple sources: repeat DBS, repeat rapid tests, HIV+ self-reports and clinic visits. Date of seroconversion was estimated using a random point approach. The HIV care status, for each day following seroconversion (M0), was computed using additional data collected on CD4 count, ART prescription, viral load and migration out of the trial area. Follow-up was right-censored by dates of death or trial closure if alive.We observed 565 individuals acquiring HIV (244 in intervention arm; 321 in control arm). Among them, one year after seroconversion (M12), 22% out-migrated from the trial area. 57% were diagnosed (aware of their HIV status), 27% were actively in HIV care, 12% were on ART, and were 10% virally suppressed. The cascade was comparable in both trial arms, except for ART coverage, higher in the intervention arm (15%) than in the control arm (9%).The observed cascade of care was suboptimal in seroconverters despite the introduct
Keywords: African Research